Innovative sample preparation techniques in food analysis: the rise of compressed fluids and novel solvents - Luana C. dos Santos; Juan Felipe Grisales-Mejía; Monique Martins Strieder; Jose A. Mendiola; Elena Ibáñez (Advances in Sample Preparation)
Compressed fluids and novel green solvents represent the most promising approaches for achieving sustainable sample preparation in food analysis. Traditional extraction techniques often rely on toxic organic solvents and energy-intensive processes, leading to environmental concerns and inefficient workflows. Green Analytical Chemistry (GAC) promotes the adoption of eco-friendly alternatives that minimize solvent consumption, reduce waste, and enhance extraction efficiency. This review explores the role of compressed fluids’ technologies, including Pressurized Liquid Extraction (PLE), Supercritical Fluid Extraction (SFE), and Gas-Expanded Liquid Extraction (GXL) as viable replacements for conventional solvent-based methods. These techniques offer high selectivity, shorter extraction times, and lower environmental impact. Additionally, novel solvents such as deep eutectic solvents (DES), bio-based alternatives, and gas-expanded liquids present sustainable solutions that improve biodegradability, safety, and solvent recyclability. By integrating these innovative approaches into analytical workflows, food analysis can align with Green Chemistry principles while maintaining high analytical performance. This review critically evaluates the latest advancements in green sample preparation techniques based on pressurized fluids, highlighting their transformative potential in food safety, authenticity verification, and bioactive compound extraction.